Effectiveness of the influenza and Tdap vaccination educational module (InTroDuce-Programme) on knowledge and intention for antenatal vaccination: a cluster randomised controlled trial protocol among pregnant women in Malaysian primary care clinics - Lau, Hung Chiun; Sekawi, Zamberi; Ching, Siew Mooi; Bakar, Norhasliza Abu; Dapari, Rahmat; Mohamed Alias, Siti Rohani; Talib, Nor Hazlin; Dzulkifli, Izzah Hazwani; Alwi, Nadiah Md; Hamid, Habibah Abdul; Din, Hazwan Mat (Public Library of Science, 2026)
Background Vaccination during pregnancy represents a critical public health strategy to safeguard both mothers and infants against infections such as influenza and pertussis. However, uptake remains suboptimal both globally and in Malaysia, with influenza vaccine coverage persistently low and limited awareness of Tdap recommendations. These gaps are of concern given the heightened risk of severe illness and adverse pregnancy outcomes among pregnant women, and the vulnerability of infants under two months to pertussis-related morbidity and mortality. Aims This study aims to develop, implement, and evaluate the effectiveness of a theory-driven digital education module (InTroDuce-Programme) in improving maternal knowledge, attitudes, and intention to receive influenza and Tdap vaccines during pregnancy. Methods This is a cluster randomised controlled trial to be conducted between 15 July 2025 and 14 July 2027 across four public primary care clinics in Hulu Langat, Malaysia. Two clinics will be randomly allocated to the intervention arm and two to the control arm. A total of approximately 351 pregnant women aged 18 years or older and up to 27 weeks’ gestation will be recruited. The intervention group will receive the InTroDuce-Programme, a web-based video module in Bahasa Melayu, delivered during antenatal visits, while the control group will receive standard care. Data will be collected at baseline, immediately post-intervention (intervention group only), and one-month follow-up using a validated questionnaire. Primary outcomes are changes in vaccination knowledge and intention to vaccinate. Secondary outcomes include attitudes, perceived barriers, and associations with sociodemographic and clinical factors. Data will be analysed using descriptive statistics and Generalised Estimating Equations to account for cluster effects and repeated measures. Conclusions This study will provide context-specific evidence on whether a digital, culturally tailored, Health Belief Model-based intervention can improve maternal vaccination literacy and intention in Malaysia. If effective, the InTroDuce-Programme could be integrated into routine antenatal care and inform broader maternal immunisation strategies in similar middle-income settings.